Psychiatric client embracement on primary health care - Jaciara Aparecida de Jesus Silva (Bioscience Journal, 2015)
This study aims to meet the professionals interviewed, identify the way nurses work facing the client with psychological distress and their knowledge on the concept of mental health and mental illness. This is a descriptive study, with a qualitative approach. The sample consisted of 26 nurses of the Family Health Strategy - FHS. According to Minayo, four categories emerged from data analysis: Embracement, Absence of actions for social reintegration, Orientation, Meanings. There is no differentiation between embracement and actions for social reintegration. Family approach is done through guidance. The concept of mental health has been defined as well-being, and mental illness, the presence of diseases and/or disorders.